Can Surgeons Identify Appendicitis Macroscopically? Results From a Multicentre Prospective Study. Issue 5 (October 2019) - Thong, Da Wei; Crouch, Stephen; Morgan, Samuel; Arthur, Thomas
Abstract : Purpose: The primary outcome was to investigate the accuracy of intraoperative macroscopic diagnosis by the operating surgeon with the results of the subsequent histopathologic examination. The secondary outcome was to identify the predictors of discrepancies between these 2 groups. Materials and Methods: A multicentre, prospective, observational study was conducted over a period of 2 months with a 30-day follow-up period. Patients who underwent surgery with the intention of appendicectomy were recruited in the study. Results: A total of 1169 patients were recruited. False negatives (FNs) were defined as a normal macroscopic diagnosis but histopathologically appendicitis, whereas false positive otherwise. Overall, FN rates were 22.4%, whereas false positive rates were 8.2%. The seniority of the operating surgeons did not affect the ability to accurately diagnose appendicitis macroscopically ( P =0.069). However, consultant surgeons had the lowest FN rate of 15.6%. Females and preoperative ultrasound scan increased odds of FN, whereas preoperative computed tomography decreased the odds of FN appendicectomy. Conclusion: Macroscopic identification intraoperatively is inaccurate with a FN rate of 22%.